A multicenter study of clinical impact of variant of uncertain significance reclassification in breast, ovarian and colorectal cancer susceptibility genes. (24th November 2022) - Makhnoon, Sukh; Levin, Brooke; Ensinger, Megan; Mattie, Kristin; Volk, Robert J.; Zhao, Zhongming; Mendoza, Tito; Shete, Sanjay; Samiian, Laila; Grana, Generosa; Grainger, Andrew; Arun, Banu; et al.
Abstract: Background: Clinical interpretation of genetic test results is complicated by variants of uncertain significance (VUS) that have an unknown impact on health but can be clarified through reclassification. There is little empirical evidence regarding VUS reclassification in oncology care settings, including the prevalence and outcomes of reclassification, and racial/ethnic differences. Methods: This was a retrospective analysis of persons with and without a personal history of cancer carrying VUS (with or without an accompanying pathogenic or likely pathogenic [P/LP] variant) in breast, ovarian, and colorectal cancer predisposition genes seen at four cancer care settings (in Texas, Florida, Ohio, and New Jersey) between 2013 and 2019. Results: In 2715 individuals included in the study, 3261 VUS and 313 P/LP variants were reported; 8.1% of all individuals with VUS experienced reclassifications and rates varied significantly among cancer care settings from 4.81% to 20.19% (overall p  < 0.001). Compared to their prevalence in the overall sample, reclassification rates for Black individuals were higher (13.6% vs. 19.0%), whereas the rates for Asian individuals were lower (6.3% vs. 3.5%) and rates for White and Hispanic individuals were proportional. Two‐year prevalence of VUS reclassification remained steady between 2014 and 2019. Overall, 11.3% of all reclassified VUS resulted in clinically actionable findings and 4.6% subsequently changed individuals' clinical managements. Conclusions: The findings from this large multisite study suggest that VUS reclassification alters clinical management, has implications for precision cancer prevention, and highlights the need for implementing practices and solutions for efficiently returning reinterpreted genetic test results. Abstract : Number of reclassified unique variants of uncertain significance (VUS) by gene as a function of the total number of VUS. The number of unique VUS is shown on the right axis and that number of reclassifications are on the left axis.